First-in-Human Implantation of Gutter-Free Design Stent-Graft in in situ Fenestration TEVAR for Aortic Arch Pathology - Li, Xin; Shu, Chang; Wang, Lunchang; Li, Quanming; Fang, Kun; Luo, Mingyao; Zhang, Weichang; Zhou, Yang; Zhou, Haiyang (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To report the technology and preliminary result of gutter-free design stent-graft in in-situ fenestration TEVAR. Description: The gutter-free stent graft has nickel-titanium self-expanding skeletal, double polytetrafluoroethylene coating and an outer-skirt fabric structure (named C-skirt endograft) . The outer skirt fabric prevents endoleak from the gutter around the stent graft and fenestration. Further, the skirt structure right under the fenestration in the aortic stent graft can function as a fixation of the side-branch artery endograft. These designs have the advantages of 1) prevention of endoleak; 2) fixation tightly between the branch and aorta endograft pieces. Evaluation: A patient who was diagnosed with an aortic arch aneurysm combined with localized dissection has been successfully implanted the aortic stent graft and C-skirt endograft for the left subclavian artery. The 6-month follow-up result of the C-skirt in-situ fenestration TEVAR is satisfactory without obvious endoleak. Conclusions: The new gutter-free C-skirt stent graft is being safely and effectively used for aortic arch TEVAR. Long-term evaluation of safety, effectivity, and durability needs to be proved by future multi-center studies.